PENERAPAN METODE ROTATING TRIO EXCHANGE DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Mintarsih, Mintarsih (JURNAL SINEKTIK, 2023)
The purpose of this study is to describe the application of the Rotating Trio Exchange (RTE) Learning Method in learning Mathematics Theme 3 Objects Around Me and analyze the improvement of mathematics learning outcomes Theme 3 Objects Around Me, students of Grade III SD Negeri 1 Sumberjo in the first semester of the 2019/2020 Academic Year. This type of research is Classroom Action Research (PTK). The place of this research is in Grade III SD Negeri 1 Sumberjo. The time of this study is in the middle of the first semester of the 2019/2020 Academic Year. The subjects of the study were twenty-seven children. Data collection techniques for this study with non-test techniques and test techniques. This research data collection tool with observation sheets, photo documentation of activities and daily test questions. The result of this study is the application of the Rotating Trio Exchange (RTE) Learning Method in 9 trios and the learning outcomes from the unsatisfactory category to the satisfactory category.